Dengue Fever among Renal Transplant Recipients: A Series of 10 Cases in a Tropical Country - Costa, Silvana Daher (Am J Trop Med Hyg, 2015)
This is a case series of 10 consecutive renal allograft recipients, followed at a tertiary hospital in northeast Brazil, with a confirmed diagnosis of dengue. Five of the patients needed hospitalization. Half of them were males and age ranged from 19 to 60 years with a median of 38.2 years. They had been transplanted for a mean of 5 days to 166 months. Four patients developed dengue hemorrhagic fever (DHF). All patients had myalgia and headache. All of them, except one, had fever. Positive dengue serology (IgM) was found in all patients. No patient died. Dengue is an important infectious disease that can affect renal transplant recipients, mainly in endemic areas. Its presentation seems to be similar to that seen in immunocompetent patients.